1993
DOI: 10.1159/000196174
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pleural Tuberculosis by Detection of Specific IgG Anti-Antigen 60 in Serum and Pleural Fluid

Abstract: The objective of this study was the prospective evaluation of the IgG antibody levels to mycobacterial antigen 60 (A60) in serum and pleural fluid and their role in the diagnosis of tuberculous pleuritis. The level of IgG was measured by Elisa in 30 patients with tuberculous pleuritis and 48 control subjects with pleural effusion (24 with carcinoma, f 0 with transudative pleural effusion, 11 with empyema or parapneumonic effusion, 1 with pulmonary embolism and 2 due to systemic lupus erythematosus). The median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For this reason, in addition to the clinical and radiological characteristics, the cytological and biochemical findings can aid in diagnosing tuberculous pleuritis. At present, several tests are of great interest for diagnosing tuberculous pleural effusion, such as ADA [3,4,5], interferon-γ [4, 17, 18], lysozyme [4, 19], the polymerase chain reaction [20, 21] or specific antibodies [22]. Lymphocytic predominance in pleural fluid is the rule in tuberculous effusions [2].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in addition to the clinical and radiological characteristics, the cytological and biochemical findings can aid in diagnosing tuberculous pleuritis. At present, several tests are of great interest for diagnosing tuberculous pleural effusion, such as ADA [3,4,5], interferon-γ [4, 17, 18], lysozyme [4, 19], the polymerase chain reaction [20, 21] or specific antibodies [22]. Lymphocytic predominance in pleural fluid is the rule in tuberculous effusions [2].…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46][47] As seen in table 2 (and in online supplementary fig S1A available at http://thorax.bmj.com/supplemental), sensitivity estimates ranged from 0.26 to 1.00 and specificity estimates from 0.59 to 1.00. The specificity forest plot (online supplementary fig S1B available at http://thorax.bmj.com/ supplemental) includes 7 unique studies as 4 of the total 10 studies were conducted with the same comparison population.…”
Section: Description Of Included Studiesmentioning
confidence: 97%
“…[41][42][43][44][45][46][47][48][49] None of the studies reported the method (eg, consecutive or random) of subject selection. Only one study 48 ELISA was used in 20 studies and immunochromatography in one study.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Immunoglobulin titers against mycobacterial antigens have also been proposed based on previous trials performed on patients with tuberculosis. 66,67 Mycobacterial antigen A60 obtained from M. bovis is found in all mycobacteria species, and immunoglobulin G (IgG) titers to this antigen could potentially help to detect affected individuals. In a small series, Oliver et al found significantly higher levels of IgG antibodies in both patients with positive acid-fast smears and cultures and patients with negative smears but positive cultures.…”
Section: Diagnostic Testingmentioning
confidence: 99%